Effectiveness of a trauma triage educational programme on knowledge and skill of emergency nurses in public hospitals in the West Bank, Palestine - Mohd Awwad, Khalaf Abdelfattah (2023)
Trauma at the time of writing is the ninth leading cause of death across all age categories and is predicted to rise to the 7th leading cause of death by 2030 as a consequence of increasing treatment errors. Furthermore, the number of trauma individuals diagnosed in hospitals has grown from 1.5 in 2015, to 5 and 8 million in 2017 and 2020, respectively. Injuries are also the world's fifth leading cause of moderate to serious disability. A lack of knowledge and skill could have an effect on health outcomes in an unstable trauma triage system. As a result, trauma patients' care and the hospital's care system would be jeopardised. The study's objective was to develop, implement, and evaluate the effectiveness of a trauma triage educational programme on knowledge and skill among emergency nurses in public hospitals in Palestine. Phase one – One hundred and fifty-four emergency nurses from 11 government hospitals participated in a cross-sectional study, the data were gathered using a self-administered structured questionnaire, and knowledge and skill questionnaire was collected from March and May 2021. The data were analysed using descriptive analysis and linear logistic regression. The data were collected using a pre-tested self-administrated structured questionnaire. The study analysis was done using Statistical Package for Social Sciences (SPSS) version 24 software. All tests were estimated to be two-sided, and the statistical significance was considered to be at p< 0.05. Phase two – A single-blinded randomised control trial was conducted to evaluate the effectiveness of an advanced trauma life support programme on the knowledge and skill scores among 112 emergency nurses in public hospitals in Palestine from April to July 2021. The data were analysed using repeated measures ANOVA and T-test. Phase One – The respondent's mean age was 30.5 ± 6.74 years, with the majority (52.6%) falling into the 29-and-under age group. In terms of gender, males made up the majority of responders (61.7 %). The study of the relationship showed that there was a weak positive significant correlation between knowledge and skill in trauma triage among emergency nurses. According to the final linear regression model, emergency nurses with married marital status have higher knowledge with a score of 1.078 compared to emergency nurses with single marital status. Emergency nurses with postgraduate education have lower knowledge with a score of 1.457 compared to emergency nurses who have diploma education. Emergency nurses with 5-7 years working experience have lower knowledge with a score of 1.677 score compared to emergency nurses who have 1-3 years working experience. Emergency nurses with moderate/high skill score have a higher knowledge score, 0.076, than emergency nurses who have a low skill score. The final linear regression model for skill showed that emergency nurses with 5-7 years working experience have higher skill with a score of 7.505 compared to emergency nurses who have 1-3 years working experience. Emergency nurses with moderate/high knowledge scores have a higher skill score, 1.689, than emergency nurses who have low knowledge scores. Phase two – There were significant mean score differences between the experimental and control groups in the pairwise comparisons of the groups in terms of knowledge and skill. There were significant mean score differences in knowledge between the baseline and post-intervention in the experimental group, as well as between the baseline and the three-month follow-up, and the post-intervention and three-month follow-up, whereas there were significant mean score differences in knowledge between the baseline and post-intervention in the control group, as well as between the baseline and three-month follow-up. Phase One – Trauma triage care is the weakest link in developing-country hospitals. Low levels of knowledge and skill will harm the trauma triage system and increase medical errors in hospitals. Among emergency nurses, there was a weak positive significant correlation between knowledge and skill in trauma triage. Phase Two – The advanced trauma life support programme provides one of the most efficient ways for nurses to enhance their knowledge and skill in trauma triage in the emergency department. It is a popular programme for enhancing nursing skills. Attending a half-day or two-day advanced trauma life support programme training course can help nurses improve their knowledge and skill.